Acute Septicaemic Pasteurellosis In a Domestic Duck: Diagnostic Approach Using Conventional and Molecular Methods - K B Jyothi; Abin Klliyan Ashok; Mendu Mounika (The Indian Veterinary Journal, 2026)
Pasteurellosis remains an important bacterial disease in both domestic and wild ducks. This report details a case of acute septicemic pasteurellosis in an eight-month-old backyard Pekin duck. The bird exhibited lethargy, nasal discharge, and diarrhoea before succumbing within two days. Gross changes included pulmonary congestion, epicardial haemorrhages, and multifocal hepatic necrosis. Microscopy of blood and liver smears revealed bipolar bacteria. Bacterial isolation and biochemical tests supported identification within the genus Pasteurella. Molecular detection through PCR targeting the rpoB gene further confirmed the organism. This case underscores the threat of pasteurellosis in small-scale duck production and stresses the value of prompt diagnosis and improved biosecurity.